Development of a Sociocultural-Based Unggah-Ungguh Basa Textbook Assisted by Instagram Reels for Senior High School Students - Fifi Lia Rumita; Sri Harti Widyastuti; Shobrina Nuur Atika (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2026)
This study was conducted in response to the need for innovative, contextually relevant learning materials for teaching Unggah-ungguh Basa that align with the development of digital technology and students’ media literacy culture. This research employed a Research and Development (R&D) approach using Branch's ADDIE model. Data were collected through observations, interviews, questionnaires, tests, and were analyzed using qualitative, descriptive, and quantitative techniques. The results revealed that the developed textbook integrated QR codes linking students to Instagram Reels videos demonstrating the use of Unggah-ungguh Basa in authentic social contexts. Material expert validation achieved a score of 93%, while media expert validation reached 92.8. Furthermore, the effectiveness test showed a significant improvement in students’ learning outcomes, with the average pretest score increasing from 67.78 to 90.69 in the posttest. The N-Gain score of 71% indicated a high level of effectiveness. These findings suggest the socioculturally-based Unggah-ungguh Basa textbook, supported by Instagram Reels, is feasible and effective for senior high school learning. The integration of sociocultural content and social media-based learning resources can enhance students’ understanding of Unggah-ungguh Basa, promote meaningful language learning, and support the preservation of Javanese cultural values in the digital era.